Warm-keeping breathable double-layer fabric

By using fibers such as acrylic and viscose fiber in double-layer fabrics, combined with spandex and other fibers, the problems of poor breathability and insufficient durability of existing winter fabrics are solved, and better warmth, breathability and wear resistance are achieved. sex.

CN119408258AActive Publication Date: 2025-02-11GUANGDONG QIYUE FUTURE TECH CO LTD

Patent Information

Application Number
CN202411531806.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing winter fabrics such as flannel and coral velvet perform well in terms of warmth, but have poor breathability and are prone to sweat absorption, static electricity, hair loss and pilling, reducing wear comfort.

Method used

Double-layer fabrics with 20-70% acrylic and 25-80% viscose fiber as main components are formed through textile technology, combined with spandex as the connecting line, and fibers such as spandex, modal and polyester are further added to improve warmth and breathable , moisture permeability and wear resistance.

Benefits of technology

The double-layer fabric has achieved significant improvements in warmth, breathability, moisture permeability and wear resistance, reducing the wear and tear during use, and improving wear comfort and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110644050000041
    Figure BDA0005110644050000041
  • Figure BDA0005110644050000042
    Figure BDA0005110644050000042
  • Figure BDA0005110644050000043
    Figure BDA0005110644050000043
Patent Text Reader

Abstract

The invention relates to the field of fabrics, in particular to a warm-keeping breathable double-layer fabric. Comprising a surface layer and an inner layer, the surface layer and the inner layer are connected through a connecting line, the surface layer and the inner layer are both knitted fabrics, and the surface layer and the inner layer are both composed of 20-70% of acrylic fibers, 25-80% of viscose fibers, 0-25% of spandex, 0-25% of modal, 0-25% of polyester and 0-36% of natural fibers; the natural fiber is composed of one or more of mulberry silk, sheep wool, rabbit hair, cashmere, camel hair and cotton, the inner layer and the surface layer which are obtained through mixed spinning of the acrylic fibers and the viscose fibers have good air permeability, moisture penetrability, wear resistance and heat retention property, and the inner layer and the surface layer can be stably connected through the connecting lines. The formed double-layer fabric has better heat retention property, air permeability, moisture penetrability and wear resistance, and has the advantages of better heat retention property, air permeability and wear resistance when being used for producing clothes, and the wearing comfort and durability of the clothes are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fabrics, and more specifically, to a warm and breathable double-layer fabric. Background Art

[0002] With the development of science and technology, people's quality of life has improved, and their requirements for the quality, function, and durability of clothing have also increased. Therefore, clothing fabrics are required to be breathable, warm, and prevent pilling.

[0003] Currently, most winter clothes are made of flannel and coral fleece fabrics, which can provide good warmth retention. However, flannel and coral fleece have poor air permeability, and are prone to sweat absorption, static electricity, hair loss, pilling, etc. during wearing, reducing wearing comfort.

[0004] Therefore, two layers of knitted fabrics are fixed to form a warm double-layer fabric. The single-layer knitted fabric has better air permeability. When the double layer is set, it has better warmth retention and air permeability, thereby replacing flannel and coral fleece.

[0005] However, the current knitted thermal double-layer fabric uses cotton as the main material. Although cotton has better warmth retention and breathability, it is prone to wear and pilling during use, which reduces the durability of the fabric. Further research is needed for this. Summary of the invention

[0006] In order to obtain better warmth retention while having better air permeability, moisture permeability and wear resistance, the present application provides a warm and breathable double-layer fabric.

[0007] The present application provides a warm and breathable double-layer fabric, comprising a surface layer and an inner layer, wherein the surface layer and the inner layer are connected by a connecting line, and both the surface layer and the inner layer are knitted fabrics. The components of the surface layer and the inner layer are both composed of 20-70% acrylic fiber, 25-80% viscose fiber, 0-25% spandex, 0-25 modal, 0-25% polyester, and 0-36% natural fiber; the natural fiber is composed of one or more of mulberry silk, sheep wool, rabbit hair, cashmere, camel hair, and cotton.

[0008] In the above technical scheme, 20-70% acrylic fiber has better warmth retention, good elasticity and good strength, while viscose fiber is soft and comfortable, has good moisture absorption and good air permeability. Therefore, acrylic fiber and viscose fiber are used as the main components, and their performances are combined to make the double-layer fabric have better softness and comfort, warmth retention, moisture absorption, air permeability and wear resistance.

[0009] Mulberry silk, sheep wool, rabbit hair, cashmere, camel hair and cotton are all natural fibers with better warmth retention and moisture absorption. Therefore, after being blended with acrylic and viscose fibers, the warmth retention, breathability and moisture permeability of the double-layer fabric are further improved.

[0010] On the basis of acrylic and viscose fibers, spandex is added to further improve the warmth retention, moisture permeability and wear resistance of the double-layer fabric.

[0011] Modal has high water absorption and can be compounded with acrylic and viscose fibers to further improve the moisture permeability of double-layer fabrics.

[0012] Polyester has the advantages of quick drying and good elasticity. Therefore, after being compounded with acrylic and viscose fibers, the quick drying and wear resistance of the double-layer fabric are further improved.

[0013] The percentages in the components of this application refer to mass fractions.

[0014] Preferably, the surface layer and the inner layer are both composed of 24-26% acrylic fiber and 64-66% viscose fiber.

[0015] When the above mass fraction range is adopted, the warmth retention rate can reach more than 30%, and the air permeability, moisture permeability and wear resistance are better. Therefore, the obtained double-layer fabric has better warmth retention and air permeability, and reduces the possibility of wear and tear of the produced clothes.

[0016] Preferably, the surface layer and the inner layer are both composed of 25% acrylic fiber, 60% viscose fiber and 15% spandex.

[0017] On the basis of acrylic and viscose fibers, spandex is added to have quick-drying properties, high elasticity, wear resistance and moisture absorption. Therefore, acrylic and viscose fibers can be combined to make the resulting double-layer fabric have better softness, comfort, moisture absorption, wear resistance and breathability.

[0018] Preferably, the surface layer and the inner layer are composed of 25-71.3% acrylic fiber, 17.1-63% viscose fiber, 10-11.6% spandex, and 0-5% natural fiber.

[0019] In the above technical scheme, on the basis of acrylic fiber, viscose fiber and spandex, the added natural fiber can further improve the warmth retention, air permeability and moisture permeability, and in combination with acrylic fiber, viscose fiber and spandex, the wear resistance is better.

[0020] Preferably, the surface layer and the inner layer are composed of 25-36% acrylic fiber, 10% spandex, 36% viscose fiber, 0-25% modal, 0-25% polyester, and 4% natural fiber.

[0021] In the above scheme, acrylic fiber, viscose fiber and spandex are used as the main raw materials, and modal or polyester is added to obtain better wear resistance and warmth retention, and 4% of natural fiber is added to obtain a double-layer fabric through a textile process, which has better wear resistance, air permeability, moisture permeability and warmth retention. When it is used in clothing production, it has better warmth retention, air permeability and moisture permeability, and better durability.

[0022] Preferably, the surface layer has a grammage of 280-300 g / m 2 .

[0023] The weight of this fabric is the best choice for this application, and the obtained double-layer fabric has better air permeability, warmth retention and moisture permeability, thereby improving the comfort of wearing clothing.

[0024] Preferably, the connecting thread is spandex.

[0025] Using spandex as the connecting line can stably connect the surface layer and the inner layer, and has better wear resistance, reducing the possibility of wear.

[0026] Preferably, the double-layer fabric is a double-layer fabric that has been treated with heat preservation, and the double-layer fabric that has been treated with heat preservation is made by the following method: Step 1: Put the double-layer fabric into the first active liquid for activation treatment to make the fabric saturated with water, and then dry it to make the humidity on the surface of the double-layer fabric reach 45-55%, thereby obtaining an activated fabric; Step 2: Weigh 2.3-3.6 parts of porous silica aerogel, 0.5-0.8 parts of adhesive, 0.01-0.03 parts of OP-10, 0.002-0.003 parts of initiator, and 20-30 parts of solvent, mix them evenly, and obtain a thermal insulation treatment agent; then immerse the activated fabric in the thermal insulation treatment agent, take it out, heat it to 60-65°C, pre-cure it for 5-10s, and initially form a thermal insulation film, and vacuum dry it at 101-103°C for 3-5 minutes to form a number of pores in the thermal insulation film, so as to obtain a thermal insulation porous fabric; Step 3: Immerse the thermal insulation porous fabric in the second active liquid and dry it to obtain a thermal insulation treated double-layer fabric.

[0027] In the above process, the double-layer fabric is saturated with water and then dried until the humidity on the surface of the fabric reaches 45-55%. At this time, the fibers in the fabric absorb water, and when dried to a humidity of 45-55%, water is still trapped inside the fibers, thereby obtaining an activated fabric.

[0028] When the activated fabric is immersed in the thermal insulation treatment agent, its porous silica aerogel is easily adsorbed on the fiber surface, and under the action of adhesion, the porous silica aerogel is stably adhered. The porous silica aerogel has lower thermal conductivity, porosity, and wear resistance, and can cooperate with double-layer fabrics to achieve better warmth retention and wear resistance.

[0029] Then pre-curing is carried out. At this time, the adhesive on the surface of the fabric fiber begins to solidify into a film. The initially formed thermal insulation film covers the fiber surface of the double-layer fabric. The thermal insulation film is not completely cured. Then, it is heated to 101-103°C under vacuum and vacuum dried for 3-5 minutes. In this process, the moisture inside the yarn fiber will be completely evaporated and pass through the initial thermal insulation film, so that the thermal insulation film will form several pores during the curing process, so a porous thermal insulation film is formed on the surface of the fabric fiber, thereby improving the warmth retention and wear resistance of the thermal insulation treated double-layer fabric, and having better air permeability and moisture permeability.

[0030] The second activation liquid plays a role in reactivation and cleaning, improving the environmental friendliness and safety of the fabric.

[0031] Preferably, the particle size of the porous silica aerogel is 30-150 nm.

[0032] The porous silica aerogel in the above particle size range has better wear resistance, low thermal conductivity, and is easily adsorbed on the fiber surface of the fabric, thus achieving better warmth retention and wear resistance.

[0033] Preferably, the adhesive is composed of the following raw materials in parts by weight: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane 0.8-1.5 parts Methacryloyloxyethyl maleate 0.1-0.3 parts Ethoxyethoxyethyl acrylate 0.1-0.8 parts Initiator 0.01-0.003 parts.

[0034] By compounding and blending 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, methacryloyloxyethyl maleate, and ethoxyethoxyethyl acrylate, an adhesive with good flexibility and adhesion is formed. Therefore, more porous silica aerogel can be stably adhered to the fiber surface of the fabric, thereby improving the wear resistance and warmth retention of the fabric, while allowing the fabric to maintain better air permeability and moisture permeability.

[0035] Among them, the structural formula of methacryloyloxyethyl maleate is as follows: The structural formula of ethoxyethoxyethyl acrylate is as follows: The structural formula of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane is as follows: After the above three structural substances (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, methacryloyloxyethyl maleate, and ethoxyethoxyethyl acrylate) are blended and polymerized, the formed adhesive has better adhesion to the porous silica aerogel and the fiber surface, so that the fabric has better warmth retention, wear resistance and breathability.

[0036] Preferably, the first active liquid is composed of methacryloylethyl sulfobetaine, anhydrous ethanol and water; the second active liquid is composed of cocamidopropylamine oxide, water and anhydrous ethanol.

[0037] The methacryloylethyl sulfobetaine has better dispersibility and wettability, and is easily adsorbed on the surface of the fabric yarn fiber. When the activated fabric is immersed in the thermal insulation treatment agent and solidified, it further reacts with the adhesive under the action of the initiator, so that more porous silica aerogel is stably adhered to the surface of the fabric yarn fiber, thereby improving the wear resistance and thermal insulation.

[0038] The structural formula of methacryloylethyl sulfobetaine is as follows: The second active liquid is composed of cocamidopropylamine oxide, water, and anhydrous ethanol. Anhydrous ethanol can remove small molecular substances adhering to the surface, and water plays an auxiliary cleaning role. Cocamidopropylamine oxide has a surface active effect, thereby promoting the activation and cleaning effect, so that the fabric has the advantages of being neat and clean.

[0039] The CAS number of cocamidopropylamine oxide is 68155-09-9.

[0040] In summary, this application has the following beneficial effects: 1. The inner layer and the outer layer obtained by mixing 20-70% acrylic fiber and 25-80% viscose fiber through a textile process have better air permeability, moisture permeability, wear resistance and warmth retention, and the connecting line can stably connect the inner layer and the outer layer, so that the formed double-layer fabric has better warmth retention, air permeability, moisture permeability and wear resistance. When used to produce clothing, it has the advantages of better warmth retention, air permeability and wear resistance, and improves the wearing comfort and durability of clothing.

[0041] 2. After the double-layer fabric is activated and absorbs water for the first time, it is treated with a thermal insulation agent so that the surface of the fabric fiber is adsorbed with porous silica aerogel, and it is stabilized by an adhesive. After preliminary curing, an incompletely cured thermal insulation film is formed. After high-temperature vacuum drying, the moisture inside the fabric fiber is completely evaporated. At this time, the thermal insulation film is further cured, and the moisture passes through the thermal insulation film to form a number of pores on the thermal insulation film. The curing makes the thermal insulation film have better air permeability, thermal insulation, and wear resistance. The obtained double-layer fabric has better thermal insulation, air permeability, moisture permeability and wear resistance.

[0042] 3. After compounding and blending 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, methacryloyloxyethyl maleate, and ethoxyethoxyethyl acrylate, an adhesive with good flexibility and adhesion is formed. Therefore, more porous silica aerogel can be stably adhered to the fiber surface of the fabric, thereby improving the wear resistance and warmth retention of the fabric, while maintaining better air permeability and moisture permeability of the fabric.

[0043] 4. Methacryloylethyl sulfobetaine has better dispersibility and wettability, and is easily adsorbed on the surface of fabric yarn fibers. When the activated fabric is immersed in the thermal treatment agent and solidified, it further reacts with the adhesive under the action of the initiator, so that more porous silica aerogel is stably adhered to the surface of the fabric yarn fibers, thereby improving wear resistance and thermal insulation. DETAILED DESCRIPTION

[0044] The present application is further described in detail below with reference to the embodiments. Example

[0045] Example 1 A warm and breathable double-layer fabric comprises a surface layer and an inner layer, wherein the surface layer and the inner layer are connected via a connecting line, and the connecting line stabilizes and solidifies the surface layer and the inner layer, and the connecting line is a spandex line.

[0046] The surface layer and the inner layer are both knitted fabrics, and the surface layer is composed of 30% acrylic fiber and 70% viscose fiber, and the inner layer is composed of 30% acrylic fiber and 70% viscose fiber.

[0047] The surface layer has a grammage of 280g / m 2 The weight of the inner layer is 300g / m 2 ; The counts of the surface yarn and the inner yarn are both 40, the spandex thread count is 70D, and the connecting thread usage is 5g / m 2 .

[0048] Embodiment 2-10 The difference between Example 2-10 and Example 1 is that the ingredients of the inner layer and the surface layer are different, as shown in Table 1; Table 1 Ingredients of the inner layer and the surface layer of Examples 1-10 Embodiment 11 The difference between Example 11 and Example 10 is that the double-layer fabric is a double-layer fabric that has been treated with heat preservation, and the double-layer fabric that has been treated with heat preservation is made by the following method: Step 1: Weigh 0.1 kg of methacryloylethyl sulfobetaine, 2 kg of anhydrous ethanol, and 10 kg of water and mix them evenly to obtain a first active liquid; convey the double-layer fabric to a tank containing the first active liquid at 30° C. through a conveying device, so that the double-layer fabric is completely immersed in the first active liquid, and is activated for 5 minutes at a conveying speed of 1 m / min to make the fabric saturated with water, and then convey it to a drying device for drying, so that the humidity on the surface of the double-layer fabric reaches 45%, thereby obtaining an activated fabric.

[0049] Step 2: Weigh 2.3 kg of porous silica aerogel, 0.5 kg of adhesive, 0.01 kg of OP-10, and 10 kg of anhydrous ethanol and mix them evenly to obtain solution A; weigh 10 kg of water and 0.002 kg of initiator and mix them evenly to obtain solution B; mix all of solution A and all of solution B evenly to obtain a thermal insulation treatment agent.

[0050] Then transfer the activated fabric to a tank containing a 30℃ heat preservation treatment agent, immerse it completely for 5 minutes at a transfer rate of 1m / min, and then transfer it to a double-roll extrusion device to squeeze out the water and ethanol trapped in the activated fabric after soaking, keeping the glue wet weight of the activated fabric at 180g / m 2 , and then transferred to a 60℃ oven for curing for 5s to perform preliminary curing and form a warm film. Then transferred to a vacuum drying device, vacuum drying for 5min at a temperature of 101℃ and a vacuum gauge showing -0.1MPa, so that the warm film forms several pores and obtains a warm porous fabric.

[0051] Step 3: Weigh 0.5 kg of cocamidopropylamine oxide, 20 kg of water, and 5 kg of anhydrous ethanol and mix them evenly. Transfer the thermal insulation porous fabric to the second active liquid immersed in 30°C, completely immerse it for 1 minute, and transfer it to a drying device to dry it at 80°C for 10 minutes to obtain a double-layer fabric treated with thermal insulation.

[0052] The average particle size of the porous silica aerogel is 50 nm. The initiator is ammonium persulfate, and the adhesive is 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0053] The humidity on the surface of the fabric refers to the humidity of the surface layer.

[0054] Example 12 The difference between Example 12 and Example 11 is that the raw material composition of the thermal insulation treatment agent is different, the humidity of step 1 is different, and the process parameters of step 2 are different, as follows: Step 1: Make the humidity on the surface of the double-layer fabric reach 50%; Step 2: Weigh 3 kg of porous silica aerogel, 0.7 kg of adhesive, 0.02 kg of OP-10, and 10 kg of anhydrous ethanol and mix them evenly to obtain solution A; weigh 15 kg of water and 0.003 kg of initiator and mix them evenly to obtain solution B; mix all of solution A and all of solution B evenly to obtain a thermal insulation treatment agent.

[0055] Then transfer the activated fabric to a tank containing a 30℃ heat preservation treatment agent, immerse it completely for 5 minutes at a transfer rate of 1m / min, and then transfer it to a double-roll extrusion device to squeeze out the water and ethanol trapped in the activated fabric after soaking, keeping the glue wet weight of the activated fabric at 180g / m 2 , and then transferred to a 60℃ oven for curing for 7s to perform preliminary curing and form a warm film. Then transferred to a vacuum drying device, vacuum drying for 4min at a temperature of 102℃ and a vacuum gauge showing -0.1MPa, so that the warm film forms several pores and a warm porous fabric is obtained.

[0056] Embodiment 13 The difference between Example 13 and Example 11 is that the raw material composition of the thermal insulation treatment agent is different, the humidity of step 1 is different, and the process parameters of step 2 are different, as follows: Step 1: Make the humidity on the surface of the double-layer fabric reach 55%; Step 2: Weigh 3.6 kg of porous silica aerogel, 0.8 kg of adhesive, 0.03 kg of OP-10, and 10 kg of anhydrous ethanol and mix them evenly to obtain solution A; weigh 20 kg of water and 0.002 kg of initiator and mix them evenly to obtain solution B; mix all of solution A and all of solution B evenly to obtain a thermal insulation treatment agent.

[0057] Then the activated fabric is transferred to a tank containing a 30℃ thermal treatment agent, completely immersed for 5 minutes, with a transfer rate of 1m / min, and then transferred to a double-roll extrusion device to squeeze out the water and ethanol trapped in the activated fabric after immersion, keeping the glue wetness of the activated fabric at 180g / m2, and then transferred to a 60℃ oven for curing for 10s, for preliminary curing, and forming a thermal film. Then it is transferred to a vacuum drying device, and vacuum drying is performed for 3 minutes when the vacuum gauge shows -0.1MPa and the temperature is 103℃, so that the thermal film forms several pores to obtain a thermal porous fabric.

[0058] Embodiment 14 The difference between Example 14 and Example 11 is that the adhesive is KH550.

[0059] Embodiment 15 The difference between Example 15 and Example 11 is that there is no step 1 and step 3, and the specific process is as follows: Weigh 2.3 kg of porous silica aerogel, 0.5 kg of adhesive, 0.01 kg of OP-10, and 10 kg of anhydrous ethanol and mix them evenly to obtain solution A; weigh 10 kg of water and 0.002 kg of initiator and mix them evenly to obtain solution B; all of solution A and all of solution B are mixed evenly to obtain a thermal insulation treatment agent.

[0060] Then the double-layer fabric is transferred to a tank containing a 30℃ thermal treatment agent, completely immersed for 5 minutes at a transfer rate of 1m / min, and then transferred to a double-roll extrusion device to squeeze out the water and ethanol trapped in the soaked fabric, keeping the wet weight of the fabric at 180g / m 2 , and then transferred to a 60℃ oven for curing for 5s to perform preliminary curing and form a warm film. Then transferred to a vacuum drying device, vacuum drying for 5min at a temperature of 101℃ and a vacuum gauge showing -0.1MPa, so that the warm film forms several pores and obtains a warm porous fabric.

[0061] Example 16 The difference between Example 16 and Example 11 is that the porous silica aerogel is replaced by an equal amount of nano-silica with an average particle size of 50 nm.

[0062] Embodiment 17 The difference between Example 17 and Example 12 is that the adhesive is obtained by mixing 0.8 kg of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 0.1 kg of methacryloyloxyethyl maleate, and 0.8 kg of ethoxyethoxyethyl acrylate; and the heat preservation treatment agent is prepared by the following method: 3.6 kg of porous silica aerogel, 0.8 kg of adhesive, 0.03 kg of OP-10 and 10 kg of anhydrous ethanol were weighed and mixed evenly to obtain solution A; 20 kg of water and 0.002 kg of initiator were weighed and mixed evenly to obtain solution B; all of solution A and all of solution B were mixed evenly, then heated to 62° C. and reacted for 30 minutes to allow a preliminary reaction to occur, and then the pH value was adjusted to 7 to obtain a thermal insulation treatment agent.

[0063] Embodiment 18 The difference between Example 18 and Example 12 is that the adhesive is obtained by mixing 1.5 kg of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 0.3 kg of methacryloyloxyethyl maleate, and 0.1 kg of ethoxyethoxyethyl acrylate.

[0064] Embodiment 19 The difference between Example 19 and Example 17 is that methacryloyloxyethyl maleate is replaced by 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0065] Embodiment 20 The difference between Example 20 and Example 17 is that ethoxyethoxyethyl acrylate is replaced by 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane in an equal amount.

[0066] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the viscose fiber is replaced by modal in equal amounts.

[0067] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that an equal amount of nylon is replaced by cotton.

[0068] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of nylon is replaced by polyester.

[0069] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that an equal amount of nylon is replaced by spandex.

[0070] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that: 15% acrylic fiber and 85% viscose fiber.

[0071] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that: 85% acrylic fiber and 15% viscose fiber.

[0072] Performance testing Detection method / test method Moisture wicking: GB / T 21655.1-2008, moisture permeability; Air permeability: GB / T 5453-1997; Insulation rate: GB / T 11048-1989 Method A; Abrasion resistance: Refer to the mass loss of ASTM D4966-2012 "Determination of the Abrasion Resistance of Fabrics by the Martindale Method for Textiles". Use a Martindale Abrasion and Wear Tester with a pressure of 9 kPa to rub the surface layer of the double-layer fabric for 1300, 2000, and 3000 times to check the degree of surface wear: light, moderate, and heavy.

[0073] The above experiments were tested 5 times and the average value was taken. The specific data are shown in Table 1; Table 1 Experimental data of Examples 1-22 and Comparative Examples 1-6 Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that the warmth retention rate, air permeability and moisture permeability of Example 1 are higher than those of Comparative Examples 1 and Comparative Examples 3-4, while the warmth retention rate, air permeability and moisture permeability of Example 1 are not much different from those of Comparative Example 2, but Comparative Example 2 is prone to wear, indicating that the composite of nylon and viscose fiber of the present application has better air permeability, moisture permeability, wear resistance and warmth retention.

[0074] Combining Example 1 and Comparative Examples 5-6 and Table 1, it can be seen that the air permeability and moisture permeability of Comparative Examples 5-6 are lower than those of Example 1, while the warmth retention rate of Comparative Example 6 is not much different from that of Example 1, indicating that the present application adopts a compound of nylon and viscose fiber, and the obtained double-layer fabric has better air permeability, moisture permeability, wear resistance and warmth retention.

[0075] By comparing Example 11 with Example 10 and combining with Table 1, it can be seen that the air permeability and moisture permeability of Example 11 are not much different from those of Example 10, but the thermal insulation rate and wear resistance are significantly improved, indicating that the thermal insulation treated fabric obtained by the thermal insulation treatment process of the present application has better thermal insulation and wear resistance, and has better air permeability and moisture permeability.

[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A warm and breathable double-layer fabric, comprising a surface layer and an inner layer, wherein the surface layer and the inner layer are connected by a connecting line, and both the surface layer and the inner layer are knitted fabrics, characterized in that: The surface layer and the inner layer are composed of 20-70% acrylic fiber, 25-80% viscose fiber, 0-25% spandex, 0-25 modal, 0-25% polyester, and 0-36% natural fiber; the natural fiber is composed of one or more of mulberry silk, sheep wool, rabbit hair, cashmere, camel hair, and cotton.

2. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The surface layer and the inner layer are both composed of 24-26% acrylic fiber and 64-66% viscose fiber.

3. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The surface layer and the inner layer are both composed of 25% acrylic fiber, 60% viscose fiber and 15% spandex.

4. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The surface layer and the inner layer are composed of 25-71.3% acrylic fiber, 17.1-63% viscose fiber, 10-11.6% spandex, and 0-5% natural fiber.

5. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The surface layer and the inner layer are both composed of 25-36% acrylic fiber, 10% spandex, 36% viscose fiber, 0-25% modal, 0-25% polyester, and 4% natural fiber.

6. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The surface layer has a grammage of 280-300 g / m 2 .

7. The thermal insulation and breathable double-layer fabric according to claim 1, characterized in that: The connecting line is spandex.

8. A warm and breathable double-layer fabric according to any one of claims 1 to 7, characterized in that: The double-layer fabric is a double-layer fabric that has been treated with heat preservation, and the double-layer fabric that has been treated with heat preservation is made by the following method: Step 1: Put the double-layer fabric into the first active liquid for activation treatment to make the fabric saturated with water, and then dry it to make the humidity on the surface of the double-layer fabric reach 45-55%, thereby obtaining an activated fabric; Step 2: Weigh 2.3-3.6 parts of porous silica aerogel, 0.5-0.8 parts of adhesive, 0.01-0.03 parts of OP-10, 0.002-0.003 parts of initiator, and 20-30 parts of solvent, mix them evenly, and obtain a thermal insulation treatment agent; then immerse the activated fabric in the thermal insulation treatment agent, take it out, heat it to 60-65°C, pre-cure it for 5-10s, and initially form a thermal insulation film, and vacuum dry it at 101-103°C for 3-5min to form a plurality of pores in the thermal insulation film, and obtain a thermal insulation porous fabric; Step 3: Immerse the thermal insulation porous fabric in the second active liquid and dry it to obtain a thermal insulation treated double-layer fabric.

9. The warm and breathable double-layer fabric according to claim 8, characterized in that: The adhesive is composed of the following raw materials in parts by weight: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane 0.8-1.5 parts Methacryloyloxyethyl maleate 0.1-0.3 parts Ethoxyethoxyethyl acrylate 0.1-0.8 parts.

10. The thermal insulation and breathable double-layer fabric according to claim 8, characterized in that: The first active liquid is composed of methacryloylethyl sulfobetaine and water; the second active liquid is composed of cocamidopropylamine oxide, water and anhydrous ethanol.

Citation Information

Patent Citations

  • Fireproof thermal insulation material and preparation method thereof

    CN112759353A

  • Multifunctional knitted fabric and manufacturing process thereof

    CN116676704A

  • Hydrophobic silica aerogel blanket and method for preparing same

    US20220380222A1

Cited By

  • Preparation method of machine-washable close-fitting warm-keeping light and thin knitted fabric

    CN120925156A